Prevalence of Permanent Congenital Hypothyroidism in Children in Yazd Central Iran - Reza Soleimanizad; Azar Rabiei; Mahtab Ordooei; Fatemeh Mirjalili (Tehran University of Medical Sciences, 2013)
Background: Congenital hypothyroidism is a condition of thyroid hormone deficiency. Approximately 1 in 4000 newborn infants has a deficiency of thyroid function. The aim of this study is determination of the prevalence of permanent and transient congenital hypothyroidism (CH) in Yazd, Iran.Methods: From May 2006 to June 2008, 35377 newborns were screened by measuring serum TSH obtained by heel prick. The neonates who had a TSH≥5mU/L were recalled for measurement of serum T4 and thyroid stimulating hormone (TSH) in venous samples. Based on the results of the secondary measurements (between days 7 and 28), neonates were considered hypothyroid if their T4 was <6.5 mg/dl and their TSH was ≥10mIU/L. In 22 primarily diagnosed as cases of CH, treatment was discontinued at age 3 years for 4 weeks and T4 and TSH were measured again. Permanent or transient CH was determined from the results of these tests; Patients with TSH levels ≥5 mIU/l were diagnosed with permanent CH.Results: The incidence of congenital hypothyroidism was found to be 1:1608 with a female to male ratio of 0.69:1. In 22 patients with CH, 10 patients were diagnosed with permanent CH (45.5%) and 12 with transient hypothyroidism (54.5%). Permanent CH was associated with higher TSH levels at first measurement than transient hypothyroidism(P-value=0.041).Conclusion: The rate of transient CH in our study was higher than the comparable worldwide rate, so more and larger studies are needed to find clear information about the etiologic factors of this disease